1996
DOI: 10.1080/0028825x.1996.10410697
|View full text |Cite
|
Sign up to set email alerts
|

A synopsis of New ZealandSphagna, with a description ofS. simplexsp. nov

Abstract: Nine species of Sphagnum are documented in the New Zealand flora: S. australe, S. compactum, S. cristatum, S. falcatulum, S. novozelandicum, S. perichaetiale, S. squarrosum, S. subnitens, and S. simplex Fife sp. nov. A key to species is presented and all species are described. Sphagnum simplex, in section Subsecunda, is described and illustrated, its distribution is mapped, and ecology and systematic relationships are discussed. Sphagnum compactum is recorded from New Zealand and Australasia for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 7 publications
(12 reference statements)
2
47
0
Order By: Relevance
“…Typically pigmented (browngreen) plants of S. cristatum were also present at study area 7, and these occasionally grew intermixed with the red morphotypes. Photographs of the red ( Microscopic analysis of the 34 S. cristatum specimens collected for this study, as well as some 100 herbarium specimens from aK, BiNG, and ChR (from both the North island and the South island), showed that all (including the red morphotype) had a branch leaf chlorophyllose cell shape typical of S. cristatum, as described accurately by andrews (1951) and Fife (1996). in cross-section, the chlorophyllose cells are elliptical to urceolate and are usually well exposed on the concave (adaxial) leaf surface by a thickened end wall.…”
Section: Field and Morphological Observationssupporting
confidence: 66%
See 3 more Smart Citations
“…Typically pigmented (browngreen) plants of S. cristatum were also present at study area 7, and these occasionally grew intermixed with the red morphotypes. Photographs of the red ( Microscopic analysis of the 34 S. cristatum specimens collected for this study, as well as some 100 herbarium specimens from aK, BiNG, and ChR (from both the North island and the South island), showed that all (including the red morphotype) had a branch leaf chlorophyllose cell shape typical of S. cristatum, as described accurately by andrews (1951) and Fife (1996). in cross-section, the chlorophyllose cells are elliptical to urceolate and are usually well exposed on the concave (adaxial) leaf surface by a thickened end wall.…”
Section: Field and Morphological Observationssupporting
confidence: 66%
“…This species has been reported from a limited number of New Zealand localities (Fife 1996;Karlin & andrus 2006), and we can report a new location for S. perichaetiale on the South island. a J. K. Bartlett collection housed at aK contains a few stems of S. perichaetiale collected near Ross (westland land District).…”
Section: Sphagnum Perichaetialementioning
confidence: 64%
See 2 more Smart Citations
“…It is mainly a boreal subgenus with approximately 28-31 species known from the northern hemisphere (Gao and Crosby 1999, Iwatsuki 2004, Hill et al 2006, McQueen and Andrus 2007, Flatberg 2013. The subgenus also embraces a few species in the southern hemisphere (Eddy 1985, Fife 1996, Müller 2009). The most recent species described in subg.…”
Section: Introductionmentioning
confidence: 99%